AB0634 Utility of 18F-FDG PET/CT in a Subset of Patients with Atypical Manifestations of Large-Vessel Giant Cell Arteritis (LV-GCA). (9th June 2015) - Sopeña, B.; Díaz-Peromingo, J.A.; Alende, V.; Domínguez Prado, I.; Carballo, I.; Pombo-Pasín, M.; Freire, M.D.C.; González-Quintela, A.
Abstract : Background: Some patients with LV-GCA does not have cranial symptoms of giant cell arteritis (C-GCA) and the temporal artery biopsy (TAB) is negative for arteritis. This subset of patients usually has diagnostic delay and inappropriate treatment [1]. Furthermore, patients with biopsy-proven C-GCA and isolated ESR increase could be erroneously considered as a relapse and put on steroid treatment. In these 2 groups of patients, where clinical decisions are difficult the 18F-FDG PET/CT scan may be useful Objectives: To study if the realization of a PET/CT with 18F-FDG can be helpful for the diagnosis of difficult cases of LV-GCA and to evaluate relapses in patients with diagnosed C-GCA and elevated markers of inflammation Methods: Since January 2012 two groups of patients, who agree to participate, were prospectively studied at our Hospital: Group 1: Patients with clinical suspicion of C-GCA but with a negative TAB and/or patients with inflammatory general syndrome of unknown origin who did not meet criteria for C-GCA [1]. Group 2: patients with biopsy-proven C-GCA and ESR persistently elevated where relapse was considered. In the 2 groups, once the diagnostic work-up has ended, an 18F-FDG PET/CT was performed Results: A total of 22 patients were studied, 17 were women (77%) with a mean age of 72 years (range: 50-85 years). Group 1 (n=18): The main complaint was: constitutional symptoms in 13 (72%), fever of unknown origin 7 (39%), optic neuritis 1 and relapsing polymyalgia rheumatica (PMR) in another. Symptoms of upper or lower extremity claudication were present in 8 (44%) and 1 (6%) respectivelysevere, abdominal pain in 4 (22%), no patient had stroke. 4 patients (all with normal TAB) had temporal artery abnormalities. Anemia was documented in 10 patients (55%) and ESR>50 in 18 (mean 96; range: 52-140 mm/h). TAB was performed in 9 patients and was negative in all cases. PET data showed vascular uptake suggestive of LV-GCA without temporal enhancement in 16/18 (89%). No patients with a negative PET have LV-GCA: the optic neuritis was caused by B. henselae and the other improved without treatment. The patient previously diagnosed with PMR showed vascular enhancement so this information changed the treatment. In the 4 patients with abdominal pain intense uptake of the abdominal aorta was seen. Group 2 (n=4): all patients had ESR>100 mm/h. 1 patient had symptoms of PMR and the other 3 were asymptomatic. However, 2 patients were on intermittent treatment with steroids. The PET/TC was negative for arteritis in 3 patients which were followed without treatment during a mean of 16.5 months. In the other case, the PET/TC images were typical of PMR (without signs of LV-GCA) and had a good response to low doses of steroids Conclusions: The judicious use of PET/CT was useful in the diagnosis and management of selected cases of LV-GCA and to avoid unnecessary steroid treatments in patients without vasculitis or relapse References: Weyand CM, Gorozny JJ. Gian-Cell Arteritis and Polymyalgia Rheumatica. N Engl J Med 2014; 371:50-7. Disclosure of Interest: None declared